A Preliminary Guide for Assertive Selection of Active Methodologies in Software Engineering Education - Lima, José; Alencar, Fernanda; Santos, Wylliams (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2021)
The use of Active Methodologies (AMs) in Software Engineering (SE) teaching has provoked scenarios that provide students with more meaningful learning, bringing the academy and the industry closer to stimulate transversal competencies and analytical skills through a humanistic, critical and reflective education. Despite this, the use of AMs in the SE teaching-learning process presents some obstacles, such as the low understanding by professors, the choice of the appropriate type for the teaching context, time and effort required to prepare the classes, and the absence of support tools, making implementation a challenge. In order to mitigate these difficulties, this article aims to present the development of a selection guide that provides professors with a tool to assist them in the assertive choice of the type of active methodology, based on the identifying the student’s learning profile and style. The guide has been developed through the Design Science Research methodology. Its first version was validated through a cycle of focus groups session with a panel composed of experts in the educational context of SE and in the use of AMs. The results showed indications of its usefulness, clarity, ease of use, organization, flexibility, pedagogical appropriateness, visualization and selection of AMs in different teaching contexts. In this sense, these actions can be carried out with a low level of effort by professors with few skills.